2016
DOI: 10.1016/j.watres.2016.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Shielding membrane surface carboxyl groups by covalent-binding graphene oxide to improve anti-fouling property and the simultaneous promotion of flux

Abstract: a b s t r a c tGraphene oxide (GO) is an excellent material for membrane surface modification. However, little is known about how and to what extent surface functional groups change after GO modification influence membrane anti-fouling properties. Carboxyl is an inherent functional group on polyamide or other similar membranes. Multivalent cations in wastewater secondary effluent can bridge with carboxyls on membrane surfaces and organic foulants, resulting in serious membrane fouling. In this study, carboxyls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…Although the surface energy is higher (lower contact angle) compared to the PTFE membrane, the permeable graphene film exhibits a negligible surface charge (remains charge neutral) compared to the negatively charged PTFE membrane. Charge neutrality generally helps improve the membrane’s antifouling properties, and is likely to be the case in this work 38 , 39 .…”
Section: Discussionmentioning
confidence: 82%
“…Although the surface energy is higher (lower contact angle) compared to the PTFE membrane, the permeable graphene film exhibits a negligible surface charge (remains charge neutral) compared to the negatively charged PTFE membrane. Charge neutrality generally helps improve the membrane’s antifouling properties, and is likely to be the case in this work 38 , 39 .…”
Section: Discussionmentioning
confidence: 82%
“…Also, Cu(NO 3 ) 2 and ethanol amine have been used to form stable nano-strand-channelled GO ultrafiltration membranes, comprising a network of nano-channels after the ethanol amine was washed away by N 2 H 4 (Huang et al 2013). Very recently, it has been shown that GO nanosheets could be modified/connected by solvent green (8-hydroxy-1,3,6-pyrenetrisulfonic acid trisodium salt) through the strong π-π stacking interactions (Shen et al 2017) or by ethylenediamine (Han et al 2016).…”
Section: W Yu Et Almentioning
confidence: 99%
“…Applying an electric capacitive carbon material (e.g., activated carbon) as the supporting layer of the UF membrane could also increase the electrostatic repulsion when negatively charged (Liang et al, 2019). The membrane-foulant covalent complexation could be alleviated by reducing the density of carboxyl groups on the membrane surface (Mo et al, 2012;Han et al, 2016). The spatial effects could be regulated by changing the pore morphology (Xiao et al, 2014a;Fan et al, 2018), surface roughness (Hashino et al, 2011;Feng et al, 2017), and surface topography of the membrane (e.g., prism/pyramid/embossing-patterned membranes Won et al, 2016 and hierarchically textured membranes Zhao et al, 2018).…”
Section: Membrane Modification For Tuning the Membrane-foulant Interamentioning
confidence: 99%